Menyoroti Tren Kesalahan Berbahasa dalam Konten Iklan Produk Kecantikan di Media Sosial Instagram - Jasmine Malaika Ramadhani; Raihana Virza Aulia Lestari; Fakhri Ardan Naashir; Hanifah Mahiroh Azizah; Hindun Hindun (Populer: Jurnal Penelitian Mahasiswa, 2024)
This study aims to identify and analyze language errors in beauty product advertisements on the Instagram account of MS Glow Beauty. Using a descriptive qualitative approach, data were collected through screenshots of various advertisement posts from the account. The analysis focused on identifying spelling errors, grammatical inaccuracies, and language interference within the advertisement content. The findings revealed significant language errors, including inappropriate word usage, incorrect sentence structures, and inconsistent mixing of Indonesian and English. These errors can reduce the professionalism and effectiveness of marketing communications and influence consumer perceptions of the product and brand. The study highlights the importance of proper and consistent language use in digital marketing content to enhance communication quality and brand image. Recommended language improvements are expected to help beauty brands increase the appeal and effectiveness of their social media advertisements, contributing to better practices in digital marketing.